FAKTOR PREDISPOSISI DAN REINFORCING YANG MEMPENGARUHI MINAT AKSEPTOR KB IUD PADA PANDEMI COVID-19 DI KELURAHAN PUSPANEGARA BOGOR - R.A, Mella Yuria; Gustina, Irwanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Indonesia's population growth tends to increase every year, with an estimated population of 237.6 million people. One of the strategies for implementing the family planning program is to increase the use of IUD contraceptives. IUD contraceptive applicants in West Java are still very low, namely only 9.07%, different from DKI Jakarta Province IUD acceptors of 17.69 %. In December 2019 WHO declared the COVID-19 virus a global health emergency. This condition has an impact on the continuity of public health services, including family planning services. The aim of this research is to determine the predisposing and reinforcing factors that affect the interest of IUD family planning acceptors during the Covid-19 pandemic in Puspanegara Village, Bogor. The design of this study used a descriptive analytic with a cross sectional research design. The total sample was 50 active family planning acceptors. Analysis of the data used with the Chi Square Test. The results showed that out of 50 respondents as many as 45 respondents (90%) were not interested in using the IUD KB. This was influenced by predisposing factors for age (p value 0.001), parity (p value 0.002), knowledge (p value 0.004) and reinforcing factors for family planning services (p value 0.001). The conclusion of this study is the low interest of reproductive age couples to become IUD family planning acceptors during the Covid-19 pandemic.